Challenges to Conducting Health Information Exchange Research and Evaluation: Reflections and Recommendations for Examining the Value of HIE. Issue 1 (4th September 2017) - Yeager, Valerie A.; Vest, Joshua R.; Walker, Daniel; Diana, Mark L.; Menachemi, Nir
Introduction: Health information exchange (HIE) promises cost and utilization reductions. To date, only a small number of HIE studies have demonstrated benefits to patients, providers, public health, or payers. This may be because evaluations of HIE are methodologically challenging. Indeed, the quality of HIE evaluations is often limited and authors frequently note unmet evaluation objectives. We provide a systematic identification of HIE research challenges that can be used to inform strategies for higher quality scientific evidence. Methods: We conducted qualitative interviews with 23 HIE researchers and leaders of HIE efforts representing experiences with more than 20 HIE efforts. We also conducted a six-person focus group to expand on and confirm individual interview findings. Qualitative analysis followed a grounded theory approach using multiple coders. Results: Participants experienced similar challenges across seven themes (i.e., HIE maturity, data quality, data availability, goal alignment, cooperation, methodology, and policy). Conclusion: Several options may exist to improve HIE research, including developing better conceptual models and methodological approaches to HIE research; formal partnerships between researchers and HIE entities; and establishing a nationwide database of HIE information. Our proposed approaches of promoting data availability, resource sharing, and new partnerships can help to overcome existing barriers and facilitate HIE research.